Which factors are associated with COVID-19 infection incidence in care services for older people in Nordic countries? A cross-sectional survey. Issue 6 (August 2022) - Rauhala, Auvo S.; Fagerström, Lisbeth M.; Lindholst, Andrej C.; Sinervo, Timo S.; Bertelsen, Tilde M.; Bliksvær, Trond; Lunde, Bente V.; Solli, Rolf; Wolmesjö, Maria G.; Hansen, Morten B.
Aims: To investigate the differences between Sweden, Denmark, Finland and Norway regarding residential/home care units' and frontline managers' background factors, the resources allocated and measures taken during the initial phases of the COVID-19 pandemic, and whether and how these differences were associated with COVID-19 among older people in residential/home units. Methods: Register- and survey-based data. Responses from managers in municipal and private residential/home units. Number of municipal COVID-19 cases from national registries. Multilevel logistic multivariate regression analysis with presence of COVID-19 among older people in residential/home units as the outcome variable. Results: The proportions of residential/home units with client COVID-19 cases, mid-March–April 2020 were Denmark 22.7%, Finland 9.0%, Norway 9.7% and Sweden 38.8%, most cases found in clusters. The proportions were similar among employees. Client likelihood of having COVID-19 was six-fold higher if the employees had COVID-19. Mean client cases per residential/home unit were Denmark 0.78, Finland 0.46, Norway 0.22 and Sweden 1.23. For the same municipal infection incidence class, Sweden's mean client infection levels were three-fold those of other countries. The regression analysis variables country, municipal COVID-19 incidence proportion, and care type were associated with client cases at p ⩽ .001. Compared with Denmark, the odds ratios (ORs) for Sweden, Norway and Finland were 1.86, 0.41 and 0.35 respectively. The variable difficulties in preventive testing had an OR of 1.56, p  ⩽ .05. Conclusions: Municipal COVID-19 incidence, employee cases, and the lack of testing resources somewhat explained the confirmed COVID-19 cases among older people in residential/home units. A two- to five-fold unexplained inter-country difference in ORs in the multivariate analyses was notable. The level of protection of vulnerable older clients in municipal and private residential/home units differed between the included countries.